Diagnostic value of linear and non-linear analyses of heart rate variability for differentiation of homeostasis in health status, disease state, or death in dogs - Martinello, L. M. [UNESP]; Romao, F. G. [UNESP]; Godoy, M. F.; Machado, L. H. A. [UNESP]; Tsunemi, M. H. [UNESP]; Lourenco, M. L. G. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2024)
The autonomic nervous system is closely linked to heart rate and is characterized as a chaotic deterministic system. As the heart is therefore controlled by a non-linear system, these analyzes are being used more and more. The aim of this study was to evaluate nonlinear indices of recurrence graphs and linear indices in healthy, sick and at risk of death dogs and to demonstrate whether these indices have good diagnostic accuracy to identify dogs at risk of death. Sixty-six dogs underwent heart rate variability analysis using a frequency meter. The results showed that the SDNN, RMSSD, PNN50% and DET% indices showed a significant difference between all groups, helping to differentiate the health status in terms of autonomic homeostasis. Greater sensitivity (96.67%) was observed for linear indices (SDNN, RMSSD and PNN50%) and greater specificity (100%) for non-linear indices (DET%, REC% and LAM%) in the recognition of dogs at risk of death. Linear indices (SDNN, RMSSD and PNN50%) and non-linear indices (DET% and ShanEnt) showed greater diagnostic accuracy for identifying healthy or dying dogs. It is concluded that the studied indices of heart rate variability help to differentiate the health status in healthy dogs and are excellent predictors of prognosis.
Keywords: Autonomic nervous system; Heart rate variability; Heart rate monitor; Chaos theory; canine